Pharmacoepidemiologic And Cost Evaluation Of Off-Label Drug Prescribing Among Paediatric Patients At Hospital Sungai Buloh, Selangor, Malaysia - Balan, Shamala (2018)
Off-label drug prescribing is common among paediatric patients. Prevalence and cost data on off-label drug prescribing among paediatric patients in Malaysia as well as the reasons behind the quantitative findings of previous studies remains unexplored. This research aimed to explore, evaluate and characterise the practice of off-label prescribing among paediatric patients in Hospital Sungai Buloh. Four studies were conducted using mixed-methodology approach to address the research objectives. The qualitative method provided a baseline and ground information on the awareness, knowledge, attitudes and views on off–label drug prescribing among paediatric patients.